How do low-carbon city policies shape older adults health? Evidence from environmental and mobility pathways in China - Yue, Xiaonan; Li, Yudi (Frontiers in Public Health, 2025)
ObjectivesAs environmental pollution and population aging become increasingly severe, it is especially important to assess the health co-benefits of climate-related urban policies. This study aims to examine the impact of China’s Low-Carbon City Pilot Program (LCCP) on the health of the older adults. It focuses on potential mechanisms such as improvements in environmental quality and increases in non-motorized transportation.MethodsThis study uses a multi-period Difference-in-Differences (DID) approach to evaluate the health effects of the LCCP. The analysis draws on nationally representative panel data from the China Family Panel Studies (CFPS) between 2012 and 2018. The sample is restricted to individuals aged 60 and above. The main outcome variable is self-rated health, with frequency of medical visits used as a supplementary indicator. The treatment variable is defined based on the official list of low-carbon pilot cities and their launch years. The analysis controls for various individual, intergenerational, and household-level characteristics. To explore possible mechanisms, the study conducts mediation analysis focusing on perceived environmental quality and non-motorized travel behavior. It also includes commuting distance and commuting time as moderating variables to assess the limiting effect of spatial accessibility.ResultsThe results show that the LCCP significantly improved the health of older adults. The DID estimates indicate a positive policy effect that remains robust across alternative model specifications and when using other outcome variables such as medical visit frequency. The mediation analysis suggests that improvements in environmental quality—especially in subjective environmental perceptions—and increases in non-motorized travel are key channels for health improvement. In addition, the health benefits of the policy are more pronounced among older adult individuals who face longer commuting distances and times. Subgroup analysis further reveals heterogeneous effects: the policy yields greater health improvements for males, rural residents, and the younger older adults (aged 60–69). Overall, these findings support the proposed hypotheses and highlight both the direct and indirect health benefits of China’s low-carbon urban transition.ConclusionThis study concludes that the LCCP significantly enhanced older adults health by improving environmental quality and travel behavior. The health effects are stronger for groups with better spatial accessibility and are partially realized through household perceptions and increased non-motorized travel. The results emphasize the importance of integrating environmental policies with age-friendly planning in urban governance to promote healthy aging.